The economic burden of the care and treatment for people with Alzheimer's disease: the outlook for the Czech Republic - Marešová, Petra; Zahálková, Veronika (Neurological sciences, 2016)
The aim of this paper is to specify the cost of treatment and care for people with Alzheimer's disease (AD) in the Czech Republic and also with a view to the future. Data availability is evaluated as well as the quality of cost comparison with other developed countries. Data for the Czech Republic will include data from the health insurance company regarding medicines and treatment, as well as a selected home caring for people with dementia and, ultimately, the Social Security Administration. The basic methods include an analysis of data from publicly available sources, direct interviews with the representatives of nursing homes caring for people with dementia and the representative of the Social Security Administration of the Czech Republic. Items will be specified within the category of direct costs. For the study, the indirect costs related to the loss of patient as well as caring person productivity are not considered. Costs for treatment and care are based from the data on 4162 patients, the costs of a bed from data on 391 beds in homes for the elderly. The average annual cost per patient with AD in the Czech Republic was calculated and came to the amount of 12,783 EUR. These items include outpatient care, inpatient care in a medical facility, inpatient care in homes and medications. In terms of share of these items on the direct costs, the largest item are services provided by special homes which contributes to the direct costs by 94 %, medications create 1 % and treatment (both outpatient and inpatient) 5 %. In the case of home care the total costs are lower at 4698 EUR. The Czech Republic as well as other developed countries are faced with the problem of unified accounting cost of people suffering from Alzheimer's disease. This then causes the calculation of the economic burden to be very difficult and indicative values.
Keywords: Female; The costs of treatment and care; ambulantní péče; antipsychotika; Antipsychotic Agents; náklady na zdravotní péči; ženské pohlaví; longitudinální studie; lidé; Cost of Illness; hospitalizace; Ambulatory Care; The economic burden; Male; Alzheimer’s disease; náklady a analýza nákladů; Czech Republic; Alzheimer Disease; Hospitalization; Alzheimerova nemoc; Česká republika; mužské pohlaví; The Czech Republic; Health Care Costs; osobní újma zaviněná nemocí; Longitudinal Studies; Costs and Cost Analysis; Humans